Effects of different cooking methods and time intervals on physico-chemical and antioxidant properties of Golden pumpkin (Cucurbita maxima) - Nurshahira Mohd Shamsuri; Fauziah Tufail Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2019)
Effect of different cooking methods with different cooking time on the chemical, physical and antioxidant composition of golden pumpkin (Cucurbitae maxima) was evaluated. Pumpkin flesh has been treated with different cooking methods, which were boiling, steaming and stir-frying at different cooking time (5 and 10 minutes). Chemical analysis showed there was no significant difference (p>0.05) detected for all treatments except for the fat content in stir-fried sample. Colour analysis, which was measured using tristimulus colorimeter showed decreasing of lightness (L*) in all treated samples compared to fresh sample. Total phenolic content was determined using Folin-Ciocalteu method and the antioxidant activity was based on the evaluation of free-radical scavenging activity (DPPH assay). Total carotenoids were measured using spectrophotomer by comparing with β-carotene as the standard. Among treated samples, total phenolic content was found the highest in steamed sample. Heat treatment was found to affect the antioxidant activity in all treated samples, as the percentage of DPPH inhibition was slightly lower than fresh sample. Surprisingly, β-carotene was found to be slightly higher in steamed sample compared to other cooking methods and fresh sample. This study showed that different cooking methods gave some affect to the available antioxidant properties in golden pumpkin.